Assessing the efficiency of the geographical distribution of telecommunications network towers in the North Municipality of Riyadh (Jasmine District Case Study) - AL-Labid, Sana Saeed (Journal of natural sciences, life and applied sciences, 2022)
The study aims to the efficiency of the distribution of communication towers in the Al-Yasmeen neighborhood, located in the north of Riyadh, using GIS represented by the ARCMAP 10.8 program to determine the distribution patterns of the 63 towers affiliated with the Saudi Telecom Company, Mobily and Zain and their service to the residents of the neighborhood. The towers took the aggregate pattern with a value of 0.63. The most important results of the study were that there is inefficiency in the distribution of towers in the neighborhood. The study recommended the need to reconsider structuring the spatial distribution of communication towers in the neighborhood according to planning standards so that there is parity between the distribution of towers within the neighborhood and the area of the neighborhood and the number of people in the same neighborhood.